Rapid access to dibenzohelicenes and their functionalized derivatives - Jančařík, Andrej; Rybáček, Jiří; Cocq, Kevin; Vacek Chocholoušová, Jana; Vacek, Jaroslav; Pohl, Radek; Bednárová, Lucie; Fiedler, Pavel; Císařová, Ivana; Stará, Irena G; Starý, Ivo (Angewandte Chemie (International ed. in English), 2013)
Spiraling up: Easy access to dibenzo[5]-, dibenzo[6]-, and dibenzo[7]helicenes as well as their functionalized derivatives includes Sonogashira and Suzuki-Miyaura couplings, desilylation, and [2+2+2] alkyne cycloisomerization. The simplicity of this non-photochemical approach combined with the potential for helicity control favors dibenzohelicenes over the parent helicenes for practical applications.
Keywords: chirality; alkynes; aromaticity; asymmetric synthesis; helical structures